Immune Modules Shared by Innate Lymphoid Cells and T Cells - Robinette, Michelle L. (J Allergy Clin Immunol, 2016)
In recent years, innate lymphoid cells (ILCs) have emerged as innate correlates to T cells. The similarities between ILCs and T cells indicate that lymphocytes of fundamentally distinct lineages can share core “immune modules” that encompass transcriptional circuitry and effector functions, while utilizing non-redundant, complementary mechanisms of pattern recognition to enact these functions. We review modules currently recognized to be shared between ILCs and T cells.